2011
DOI: 10.1016/j.ajhg.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Phylogeny and the Predicted Pathogenicity of Protein Variations Reveals Equal Purifying Selection across the Global Human mtDNA Diversity

Abstract: We used detailed phylogenetic trees for human mtDNA, combined with pathogenicity predictions for each amino acid change, to evaluate selection on mtDNA-encoded protein variants. Protein variants with high pathogenicity scores were significantly rarer in the older branches of the tree. Variants that have formed and survived multiple times in the human phylogenetics tree had significantly lower pathogenicity scores than those that only appear once in the tree. We compared the distribution of pathogenicity scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
130
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 32 publications
10
130
1
Order By: Relevance
“…4B). The parameterizations in our data are similar to the previous study (28). We also confirmed that the observed value for polymorphisms with very high pathogenicity scores (>0.9) deviates from the exponential fit, indicating that forces other than purifying selection might have acted on these variants (28).…”
Section: Purifying Selection Is Less Efficient On Heteroplasmy Than Onsupporting
confidence: 79%
See 4 more Smart Citations
“…4B). The parameterizations in our data are similar to the previous study (28). We also confirmed that the observed value for polymorphisms with very high pathogenicity scores (>0.9) deviates from the exponential fit, indicating that forces other than purifying selection might have acted on these variants (28).…”
Section: Purifying Selection Is Less Efficient On Heteroplasmy Than Onsupporting
confidence: 79%
“…In the absence of natural selection, mutations are similar to random draws from all possible changes in the genome, so the selection function is expected to be equal to a constant, 1. Consistent with previous study (28), the selection function of polymorphism can be modeled by a simple function of exponential decay (R 2 = 0.9758, P = 4.71e-06; Fig. 4B).…”
Section: Purifying Selection Is Less Efficient On Heteroplasmy Than Onmentioning
confidence: 63%
See 3 more Smart Citations